Short-term forecast of oxygen concentration in nitrification chamber using artificial neural network - Płonka, Lesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the difficulties in implementing other methods of removing organic compounds and nitrogen from wastewater, municipal wastewater treatment plants use classical processes (nitrification and denitrification) that require large energy expenditure on aeration. The problem of high energy consumption concerns every treatment plant using aerobic activated sludge, hence the constant attempts to introduce possibly intelligent aeration control techniques.
Keywords: activated sludge process; nitrification chamber; artificial neural networks; osad czynny; komora nitryfikacyjna; sztuczne sieci neuronowe (SSN)